CULTURED HAIR FOLLICLE CELLS FOR THE TREATMENT OF VITILIGO - Sutnut, Piyatida; Suvanasuthi, Saroj; Viravaidya-pasuwat, Kwanchanok (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to develop a method to isolate cells from hair follicles and cultured them in a hydrogel. Methods: Different cell types obtained from hair follicles were investigated and mixed with three formulations of LutrolÂ® F-127-based hydrogels. The percentages of the cell attachment and viability were observed within 48 h. Results: The results showed that three cell types, including keratinocyte, dermal papilla, and melanocyte cells, were obtained, as shown by the expression of their corresponding genes. All formulations of the hydrogels supported cell attachment and viability. Interestingly, more than 60% cell attachment and viability were found in lutrol hydrogels supplemented with either fetal bovine serum (FBS) or heat-activated human serum. Conclusion: Higher cell attachment and viability were observed when the hair follicle cells were cultured in the hydrogel with FBS than the hydrogel with human serum. However, the lutrol gel formulation with human serum was more appropriate to be used in the future clinical study, as this formulation contained no animal-derived component.